Letter (copy) : International Solidarity Fund: foodstuffs for Spain - Tewson, Vincent
030-0179-001 Secretary's. HVT/FC/427. 19th May, 1938. The International Federation of Trade Unions, 9, Avenue d'Orsay, PARIS VIIe. Dear Sirs, INTERNATIONAL SOLIDARITY FUND - FOODSTUFFS FOR SPAIN. I understand that Mr. Schevenels has arranged with you to purchase and despatch a consignment of food supplies for Spain. The understanding is that I should send a cheque for £2,000 to enable the transaction to be put through as quickly as possible. The cheque in question is enclosed herewith. Yours sincerely, Assistant Secretary. Cheque. 292/946/30/179